1975
DOI: 10.1111/j.1755-3768.1975.tb01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benzalkonium Chloride Upon the Corneal Epithelium Studied With Scanning Electron Microscopy

Abstract: The corneal surface of rabbits and vervet monkeys was studied by means of scanning electron microscopy after the influence of the cationic surfactant, benzalkonium chloride. The concentration of the drug was 0.02% or 0.01% and the exposure time was 2 or 4 min. The corneas treated with the drug had characteristic changes with small holes or more extensive lesions of the superficial cell membranes, and loss of microvilli or microplicae. The damage was considered to be due to the lytic effect of benzalkonium chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
3

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 6 publications
(2 reference statements)
2
12
0
3
Order By: Relevance
“…These corneal epithelial images are consistent with previously published reports. [4][5][6][7]18,34 The results of the NRCE cell viability assay after exposure to travoprost additives with or without BAC were similar to the results of the TER measurements.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These corneal epithelial images are consistent with previously published reports. [4][5][6][7]18,34 The results of the NRCE cell viability assay after exposure to travoprost additives with or without BAC were similar to the results of the TER measurements.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, it also enhances corneal barrier penetration. On the other hand, numerous in vitro, ex vivo, and in vivo studies have revealed the deleterious corneal effects of BAC that include destabilization of the tear film, 1 death of corneal epithelium cells, 2,3 disruption of superficial cell membranes, loss of microvilli [4][5][6][7] and the reduction of the corneal epithelial barrier function. 8 The side effects of BAC depend both on its concentration and the period of exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these adjuvants act as ocular penetrating enhancers promoting drug penetration through the strong corneal barrier and modifying the physiochemical property of drugs (Saettone et al, 1996: Sasaki et al, 1999. At the same time, however, they destroy the corneal epithelial structure, especially the transcellular integration of superficial cells, which is mainly maintained by tight junctions (Burstein, 1980: Tonjum, 1975. Therefore, investigation of the effect on the cornea by ophthalmic drugs and adjuvants is important.…”
Section: Discussionmentioning
confidence: 99%
“…1 In ophthalmology, commonly administered pharmacotherapeutic agents contain commercially produced BAC, which consists of 3 homologs that have different N-alkyl chain lengths (C12, C14, and C16). On the other hand, numerous studies have revealed that there are deleterious corneal effects associated with BAC that include destabilization of the tear film, 2 death of corneal and conjunctival epithelial cells, [3][4][5][6] morphological changes in the corneal epithelial cells, [7][8][9][10][11] and the reduction of the corneal epithelial barrier function. [12][13][14] It has been reported in previous studies that the carbon chain lengths of phosphatidylcholines or nonionic surfactants can influence the degree of hemolysis of red blood cells.…”
mentioning
confidence: 99%